Physicochemical and Organoleptic Characteristics of Nutmeg Instant Drink (Myristica fragrans Houtt) with Variations of Maltodextrin Concentration - Rumata, Sakila; Breemer, Rachel; Picauly, Priscilia (AGRITEKNO: Jurnal Teknologi Pertanian, 2023)
Nutmeg is an export commodity that can be utilized in the food or beverage industries. Only a small portion of the nutmeg flesh is used, so the remainder is discarded as waste. Nutmeg pulp waste can be used to make an instant nutmeg powdered drink. Processing instant nutmeg drinks requires fillers such as maltodextrin to expedite drying and protect the raw materials from damage. This study aimed to determine the best maltodextrin concentration on an instant nutmeg drink's physicochemical and sensory characteristics. In this research, a completely randomized experimental design with four levels of maltodextrin treatment, including 10, 15, 20, and 25%, replicated twice, was applied. The result showed that the best treatment was a concentration of 25% because it had a moisture content of 7.42%, a vitamin C of 16.74%, a yield of 22.13%, and a water absorption of 11.50%. The sensory analysis showed that a maltodextrin concentration of 2% was slightly liked for its slightly brownish yellow color, slightly liked for its slight nutmeg aroma, and liked for its nutmeg taste.